Trop2: Jack of All Trades, Master of None - Lenárt, Sára (Cancers (Basel), 2020)
SIMPLE SUMMARY: Metastatic progression represents a major clinical challenge and remains the leading cause of death in cancer patients. Identification of suitable therapeutic targets, followed by a rational design of effective drug agents and their long-term, extensive pre-clinical and clinical testing is one of the key goals in cancer research. Trophoblast cell surface antigen 2 (Trop2) was first described as a protein highly expressed on the surface of trophoblast cells in 1981. Just recently, nearly 40 years after this discovery, sacituzumab govitecan, a Trop2-targeting antibody drug conjugate, has been granted an accelerated approval for therapy of metastatic triple-negative breast cancer, opening a new chapter of such successful story. The aim of this review is to summarize the current knowledge about Trop2 function in healthy tissue and pathology, with a special focus on its still controversial role in plasticity and heterogeneity during cancer progression. We further discuss the development and potential of Trop2-targeted therapy. ABSTRACT: Trophoblast cell surface antigen 2 (Trop2) is a widely expressed glycoprotein and an epithelial cell adhesion molecule (EpCAM) family member. Although initially identified as a transmembrane protein, other subcellular localizations and processed forms were described. Its congenital mutations cause a gelatinous drop-like corneal dystrophy, a disease characterized by loss of barrier function in corneal epithelial cells. Trop2 is considered a stem cell marker and its expression associates with regenerative capacity in various tissues. Trop2 overexpression was described in tumors of different origins; however, functional studies revealed both oncogenic and tumor suppressor roles. Nevertheless, therapeutic potential of Trop2 was recognized and clinical studies with drug–antibody conjugates have been initiated in various cancer types. One of these agents, sacituzumab govitecan, has been recently granted an accelerated approval for therapy of metastatic triple-negative breast cancer. In this article, we review the current knowledge about the yet controversial function of Trop2 in homeostasis and pathology.